2021
DOI: 10.3389/fcimb.2021.768377
|View full text |Cite
|
Sign up to set email alerts
|

A Strong Decline in the Incidence of Childhood Otitis Media During the COVID-19 Pandemic in the Netherlands

Abstract: IntroductionRecent reports have highlighted the impact of the COVID-19 pandemic on the incidence of infectious disease illnesses and antibiotic use. This study investigates the effect of the pandemic on childhood incidence of otitis media (OM) and associated antibiotic prescribing in a large primary care-based cohort in the Netherlands.Material and MethodsRetrospective observational cohort study using routine health care data from the Julius General Practitioners’ Network (JGPN). All children aged 0-12 registe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 28 publications
2
25
4
Order By: Relevance
“…In addition, recent studies demonstrated a decrease in Pediatric Emergency Department attendance during the Italian lockdown, which was particularly relevant when diagnoses as middle ear disease, and non-complicated middle ear infection were considered [20] . A similar decreasing incidence of otitis media with effusion during the lockdown period has also been observed by several authors worldwide in the last years [21] , [22] , [23] , [24] , thus supporting the clinical influence of social distancing and a reduced school attendance especially for young children.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In addition, recent studies demonstrated a decrease in Pediatric Emergency Department attendance during the Italian lockdown, which was particularly relevant when diagnoses as middle ear disease, and non-complicated middle ear infection were considered [20] . A similar decreasing incidence of otitis media with effusion during the lockdown period has also been observed by several authors worldwide in the last years [21] , [22] , [23] , [24] , thus supporting the clinical influence of social distancing and a reduced school attendance especially for young children.…”
Section: Discussionsupporting
confidence: 83%
“…Otomicroscopy, tympanometry, pure-tone or behavioral audiometry, ABR (selected cases) threshold ABR. 6 months-12 years Group A: 1/5/19–30/6/19 Vs 1/1/2020 – Vs 29/2/2020 1/5/2020–30/6/2020 Group B: 1/6/2018–30/8/2018 Vs 1/12/2018–28/2/2019 Vs 1/5/2019–30/6/2019 OME episodes; type B tympanogram Reduction of OME; Reduction of type B tympanograms Hullegie et al, 2021 [24] Nederlands Retrospective observational cohort study. Electronic health records, GP consultation, telephone consultations ≤12 years 1/3/2019–29/2/2020 Vs 1/3/2020–28/2/2021 AOM episodes; OME episodes; Ear discharge Reduction of the AOM, OME and ear discharge episodes Nguyen et al, 2021 [22] US Retrospective ≤18 years 1/3/2019–1/7/2019 vs. 1/3/2020–1/7/2020 Intraoperative effusion in OME during tympanostomy Reduction of intraoperative ear effusion Torretta et al, 2021 [18] Italy Telephone contact Mean age 41.4 ± 14 months 9/3/2020–17/3/2020 Vs 1/2/2019–30/4/2019 AOM episodes; otorrhea episodes; systemic antibiotic treatments Reduction of AOM and otorrhea episodes, and number of antibiotic treatments Allen et al, 2022 [23] US Retrospective database review of ICD-10 codes n.a.…”
Section: Discussionmentioning
confidence: 99%
“…In our study we did a sub-analysis looking at the prescription rate for respiratory tract and ear infection episodes in young children, and showed that the prescription rate remained lower during the full first pandemic year. A Dutch cohort study focusing specifically on childhood otitis media during the first pandemic year found that GP consultation declined, but antibiotic prescription rates remained similar [ 19 ]. The decrease found in our study may therefore be explained by a decrease in antibiotic prescribing for respiratory tract infections other than otitis media in this age group.…”
Section: Discussionmentioning
confidence: 99%
“…We also found a decrease of 54.01% in the prevalence of acute otitis media, similar to a multi-centre study in Italy, in which Iannella et al (19) concluded that otitis media decreased by 68.1% between March 2020 and March 2021 with respect to the same period of the previous year. In the Netherlands, primary care diagnoses of acute otitis media decreased by 63% between March 2020 and February 2021, compared to the same period the previous year (20).…”
Section: Discussionmentioning
confidence: 96%